A method for preparing a silicon / carbon aerogel composite material for a lithium ion battery negative electrode
Silicon/biomass carbon aerogel composite materials were prepared by sol-gel method and chemical vapor deposition technology, which solved the problem of first irreversible lithium loss and volume expansion of lithium-ion battery anode materials and achieved high-efficiency performance improvement of lithium-ion batteries.
Patent Information
- Application Number
- CN202410764201.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-06-14
AI Technical Summary
Existing lithium-ion battery anode materials, such as graphite and silicon, suffer from high initial irreversible lithium loss and volume expansion during cycling, resulting in poor cycle life and making it difficult to meet the needs of new energy vehicles and energy storage battery systems.
Silicon/biomass carbon aerogel composites were prepared using the sol-gel method. By employing nitrogen doping carbonization and chemical vapor deposition techniques, uniform dispersion of silicon particles and improved conductivity were achieved, mitigating volume changes and reducing the risk of contact between silicon and electrolyte.
It improves the initial charging efficiency and cycle stability of lithium-ion batteries, enhances the conductivity and lithium storage capacity of materials, reduces costs, and provides anode materials with high energy density and long cycle life.
Smart Images

Figure CN118579757B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a silicon / carbon aerogel composite material for lithium-ion battery anodes, belonging to the technical field of lithium-ion battery anode materials. Background Technology
[0002] Graphite is currently widely used as the anode material for lithium-ion batteries, but the capacity of commercial graphite anodes has already approached their theoretical specific capacity (372 mAh / g). Therefore, developing anode materials with higher specific capacity is urgently needed. Silicon anodes have a high theoretical specific capacity (4200 mAh / g) and a low electrochemical lithium intercalation potential, which perfectly meets the needs of a series of new technology fields such as new energy vehicles and energy storage battery systems.
[0003] During the first charge of a lithium-ion battery, the organic electrolyte undergoes reductive decomposition on the surface of the negative electrode, forming an SEI film that irreversibly consumes a large amount of Li from the positive electrode. + This results in low initial charging efficiency. Existing graphite materials have an initial irreversible lithium loss of 5% to 10%, while silicon materials, due to their larger surface area than graphite, have an initial irreversible lithium loss as high as 15% to 35%. In addition, the severe volume expansion of silicon anodes during cycling leads to poor cycle life and irreversible capacity, seriously hindering their further commercial application.
[0004] Carbon anode materials exhibit good cycle stability and excellent conductivity, and can buffer and accommodate the volume expansion of silicon to a certain extent. Therefore, carbon is often the preferred matrix for silicon composites. In silicon-carbon composite systems, silicon particles act as the active material, providing lithium storage capacity. Carbon can buffer the volume changes of the silicon anode during charge and discharge, improve the conductivity of silicon-based materials, and prevent silicon particles from agglomerating during charge and discharge cycles. The complementary advantages of silicon anodes and carbon composite materials result in high energy density and long cycle life in lithium-ion batteries, making them potential next-generation lithium-ion battery anode materials.
[0005] The invention patent with authorization announcement number CN 109755507 A discloses a method for preparing a silicon / carbon composite aerogel anode material for lithium-ion batteries. The method involves reacting silica aerogel with excess magnesium powder, followed by a high-temperature reaction to prepare a mixture of silica aerogel and magnesium oxide. The silica aerogel is then coated with a polymer and carbonized to prepare the silicon / carbon composite aerogel. The silica aerogel maintains the three-dimensional ordered structure of the silica aerogel, providing effective space to mitigate the volume change of silicon during charging and discharging, and suppressing damage to the electrode structure. Carbon loading onto the surface of silicon particles provides good conductivity and suppresses local polarization. However, this preparation method involves two high-temperature reactions and acid washing, making the process complex and unsuitable for commercial applications. Using high-temperature pyrolysis to coat silica aerogel with carbon to prepare silicon / carbon composite aerogels may result in poor silicon dispersion, uneven carbon layer distribution, and easy agglomeration. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a silicon / biomass carbon aerogel composite material for lithium-ion battery anodes, comprising the following steps: S1. Cut 5.28 to 7.32 parts by weight of fruit peel into pieces of the same size, put them into an aqueous solution containing 2.42 to 3.11 parts by weight of melamine, stir to mix well, soak for 12 hours, and then place them in a forced-air drying oven to dry completely to obtain nitrogen-doped carbon precursor. S2. Add 3.85-5.21 parts by mass of nitrogen-doped carbon precursor and 1.28-1.74 parts by mass of nano-silicon to deionized water, stir to mix well, transfer to a reaction vessel, seal it and place it in a constant temperature drying oven, and hydrothermally heat it at 120-250℃ for 10-20 hours to obtain a black block hydrogel. S3. Wash 2.53 to 3.48 parts by weight of black block hydrogel with solvent and place it in a freeze dryer for vacuum drying for 20 to 24 hours to obtain black block aerogel. S4, 1.45 to 2.06 parts by mass of aerogel were carbonized and chemically vapor-deposited, and then cooled to room temperature to obtain a silicon / carbon aerogel composite material with a uniform carbon layer.
[0007] Aerogels are three-dimensional network structure materials filled with a gaseous medium within a spatial network structure of gel particles, exhibiting a solid appearance. Under certain conditions, carbonization yields carbon aerogels with high porosity, lightweight and porous structure, high specific surface area, good heat resistance, and strong electrical conductivity. They can be used directly as monolithic electrode materials, making them a promising anode material for lithium-ion batteries.
[0008] A sol-gel method was used to prepare a gel in which silicon particles were dispersed. The sample was then freeze-dried to maintain its volume and structure, resulting in an aerogel material with uniformly distributed silicon particles and a porous structure. The nanoporous structure of the aerogel can serve as a storage site for silicon nanoparticles and also as a substrate for Li. + The migration path accelerates Li + This enables the transmission of materials, thereby achieving high capacity and high rate performance.
[0009] Carbon aerogels are obtained by carbonizing aerogel materials. During the carbonization process, because the diameters of nitrogen atoms in melamine and carbon atoms are similar, the substitution of carbon atoms by nitrogen atoms results in less lattice distortion, making nitrogen doping relatively easy. Nitrogen doping can introduce lone pairs of electrons from nitrogen atoms into the graphitic carbon structure, promoting rapid charge transfer and thus enhancing the conductivity and chemical activity of the material. Furthermore, the high specific surface area of carbon aerogels enables uniform dispersion and high loading of silicon nanoparticles, effectively mitigating the volume change of silicon during cycling. Simultaneously, silicon nanoparticles can fully utilize their high specific capacity, giving the composite material high lithium storage capacity and good cycling stability. Chemical vapor deposition for vapor-phase carbon coating can improve the compatibility between silicon and the electrolyte, reduce the risk of direct contact between silicon and the electrolyte during charging and discharging, and reduce capacity consumption.
[0010] As a preferred embodiment of the above technical solution, in step S1, the fruit peel is at least one selected from orange peel, grapefruit peel, watermelon peel, and tangerine peel. The stirring to mix the fruit peel thoroughly specifically involves stirring at 100–150 r / min for 2–5 hours at room temperature.
[0011] As a preferred embodiment of the above technical solution, in step S2, the particle size distribution range of the nano-silicon is 10–100 nm. The stirring to achieve homogenization specifically involves stirring at 150–200 r / min for 0.5–2 h at room temperature.
[0012] As a preferred embodiment of the above technical solution, in step S3, the solvent is ethanol and / or deionized water.
[0013] As a preferred embodiment of the above technical solution, in step S4, the carbonization specifically involves heating to 600–800°C at a heating rate of 5°C / min and holding at that temperature for 1–3 hours under an inert atmosphere. The chemical vapor deposition specifically involves, after carbonization, introducing an organic gas under an inert atmosphere, heating to 900–1200°C at a heating rate of 2°C / min, and holding at that temperature for 2–4 hours. The inert gas is at least one of nitrogen and argon. The organic gas is acetylene.
[0014] Preferably, the reaction vessel for preparing the black block hydrogel in step S2 includes a reaction vessel body, an annular plate, two sets of arc plates, a base, four sets of supports, a fixed plate, four sets of sliding rods, four sets of first sliders, a pressure plate, four sets of first springs, a hinge assembly, a buffer assembly, and a connecting assembly. An annular plate is provided on the outside of the reaction vessel body. The bottom ends of the annular plate are slidably fitted through the buffer assembly and the top of the arc plate, respectively. The bottoms of the two sets of arc plates are connected to the top of the base through the connecting assembly. Four sets of supports are evenly provided on the bottom of the base. The bottom of the fixed plate is connected to the top of the base. Four sets of sliding grooves are evenly provided on the top of the fixed plate. Each of the four sets of fixed plate sliding grooves is provided with a set of sliding rods. The four sets of first sliders are slidably connected to the fixed plate sliding grooves through a set of sliding rods. A set of first springs is provided on one end of each of the four sets of sliding rods. The tops of the four sets of first sliders are hinged to the bottom of the pressure plate through the hinge assembly, and the top of the pressure plate is in close contact with the bottom of the reaction vessel body.
[0015] More preferably, the buffer assembly includes multiple sets of damping rods and multiple sets of second springs. A set of grooves is provided at both ends of the bottom of the annular plate. The tops of the two sets of annular plate grooves are uniformly connected to the tops of the multiple sets of damping rods. The tops of the two sets of arc plates are connected to the bottoms of the multiple sets of damping rods. The tops of the two sets of arc plates are slidably fitted into the bottom grooves of the annular plate. A set of second springs is provided on the outer side of each set of damping rods.
[0016] More preferably, the connecting assembly includes two sets of arc-shaped blocks, two sets of locking blocks, and two sets of connecting screws. Two sets of arc-shaped blocks are evenly arranged on the top of the base. Each of the two sets of arc-shaped blocks has a locking groove on its top. The bottom of each of the two sets of locking blocks is engaged with the locking groove of the arc-shaped block. The top of each of the two sets of locking blocks is connected to the bottom of the arc-shaped plate. Each of the two sets of locking blocks has a threaded hole that penetrates through the arc-shaped block. The two sets of connecting screws are threadedly connected to the locking block and the arc-shaped block through the threaded hole.
[0017] More preferably, the hinge assembly includes multiple sets of hinge seats and four sets of support rods. The tops of the four sets of first sliders are respectively hinged to one end of a set of hinge seats and a support rod, and the bottom of the pressure plate is uniformly hinged to the other end of the four sets of hinge seats and support rods.
[0018] The beneficial effects that this technical solution can bring are: 1. This technical solution uses fruit peels as raw materials to prepare biomass carbon materials, which has the advantages of wide availability of raw materials, low cost, and green environmental protection; 2. In the preparation of hydrogel, when vibration occurs, it will cause the main body of the reactor to exert force and start to squeeze the pressure plate. Through the hinge assembly, the four sets of first sliders slide and start to squeeze the first spring. In the process of the expansion and contraction of the four sets of first springs and the buffer assembly, the damage caused by the force generated by vibration can be effectively reduced, and the damage caused by the force to the main body of the reactor can be reduced, thereby improving the efficiency and effect of the preparation of composite materials. 3. The nitrogen-doped carbon prepared by this technical solution helps to improve the conductivity of the material and can reduce the need for carbon additives during use, thus saving costs; 4. This technical solution has reference value for the synthesis of silicon-based anode materials for lithium-ion batteries, and provides a direction that can be explored for the development of new anode materials for lithium-ion batteries. Attached Figure Description
[0019] Figure 1 This is a flowchart illustrating the preparation process of the silicon / carbon aerogel composite material of the present invention. Figure 2 The charge-discharge curve of the silicon / carbon aerogel composite material prepared in Example 1 of this invention is shown. Figure 3 The charge-discharge curve of the silicon / carbon aerogel composite material prepared in Example 2 of this invention is shown. Figure 4 The charge-discharge curve of the silicon / carbon aerogel composite material prepared in Example 3 of this invention is shown. Figure 5 The charge-discharge curve of the silicon / carbon aerogel composite material prepared in Example 4 of this invention is shown. Figure 6 This is a schematic diagram of the reactor used to prepare silicon / biomass carbon aerogel composite material for lithium-ion battery anodes according to the present invention. Figure 7 This is the present invention. Figure 6 A magnified schematic diagram of the local structure of A; Figure 8 This is a three-dimensional schematic diagram of the hinge assembly of the reaction vessel for preparing composite materials according to the present invention; Figure 9 The graphs show the cycling performance of the silicon / carbon aerogel composites prepared in Examples 1-4. In the diagram, 1. Reactor body; 2. Annular plate; 3. Arc plate; 4. Base; 5. Support; 6. Fixing plate; 7. Sliding rod; 8. First slider; 9. Pressure plate; 10. First spring; 11. Damping rod; 12. Second spring; 13. Arc block; 14. Locking block; 15. Connecting screw; 16. Hinge seat; 17. Support rod; 18. Rotating handle; 19. Anti-slip pad; 20. Sponge pad. Detailed Implementation Example 1
[0020] S1. Cut 5.28 parts by weight of orange peel into pieces of the same size, put them into an aqueous solution containing 2.42 parts by weight of melamine, stir at 100 r / min for 2 h at room temperature, soak for 12 h, and then place them in a forced-air drying oven to dry completely to obtain nitrogen-doped carbon precursor. S2. 3.85 parts by mass of nitrogen-doped carbon precursor and 1.28 parts by mass of nano-silicon (10nm) were added to deionized water and stirred at 150 r / min for 2 h at room temperature. The mixture was then transferred to a reaction vessel, sealed and placed in a constant temperature drying oven. The mixture was hydrothermally heated at 120℃ for 20 h to obtain a black block hydrogel. S3. After washing 2.53 parts by weight of black block hydrogel with deionized water, place it in a freeze dryer and vacuum dry for 20 hours to obtain black block aerogel. S4, 1.45 parts by weight of aerogel were heated to 600°C at a heating rate of 5°C / min and held for 3 hours under nitrogen protection. Then, acetylene gas was introduced, and the temperature was further increased to 900°C at a heating rate of 2°C / min and held for 4 hours. After carbonization and chemical vapor deposition, the mixture was cooled to room temperature to obtain a silicon / carbon aerogel composite material with a uniform carbon layer. Example 2
[0021] S1. Cut 5.95 parts by weight of grapefruit peel into pieces of the same size, put them into an aqueous solution containing 2.63 parts by weight of melamine, stir at 115 r / min for 3 h at room temperature, soak for 12 h, and then place them in a forced-air drying oven to dry completely to obtain nitrogen-doped carbon precursor. S2. 4.31 parts by mass of nitrogen-doped carbon precursor and 1.43 parts by mass of nano-silicon (20nm) were added to deionized water and stirred at 170 r / min for 1.5 h at room temperature. The mixture was then transferred to a reaction vessel, sealed and placed in a constant temperature drying oven. The mixture was hydrothermally heated at 170℃ for 17 h to obtain a black block hydrogel. S3. 2.86 parts by weight of black block hydrogel were washed with ethanol and placed in a freeze dryer for vacuum drying for 21 hours to obtain black block aerogel. S4, 1.64 parts by mass of aerogel were heated to 700°C at a heating rate of 5°C / min under argon protection and held at that temperature for 2.5 h. Then, acetylene gas was introduced, and the temperature was further increased to 1000°C at a heating rate of 2°C / min and held for 3.5 h. After carbonization and chemical vapor deposition, the mixture was cooled to room temperature to obtain a silicon / carbon aerogel composite material with a uniform carbon layer. Example 3
[0022] S1. Cut 6.62 parts by weight of watermelon rind into pieces of the same size, put them into an aqueous solution containing 2.88 parts by weight of melamine, stir at 135 r / min for 4 h at room temperature, soak for 12 h, and then place them in a forced-air drying oven to dry completely to obtain nitrogen-doped carbon precursor. S2. 4.75 parts by mass of nitrogen-doped carbon precursor and 1.56 parts by mass of nano-silicon (50nm) were added to deionized water and stirred at 185r / min for 1h at room temperature. The mixture was then transferred to a reaction vessel, sealed and placed in a constant temperature drying oven. The mixture was hydrothermally heated at 210℃ for 13h to obtain a black block hydrogel. S3. After washing 3.17 parts by weight of black block hydrogel with deionized water, place it in a freeze dryer and vacuum dry for 23 hours to obtain black block aerogel. S4, 1.85 parts by weight of aerogel were heated to 750°C at a heating rate of 5°C / min and held for 2 hours under nitrogen protection. Then, acetylene gas was introduced, and the temperature was further increased to 1100°C at a heating rate of 2°C / min and held for 3 hours. After carbonization and chemical vapor deposition, the mixture was cooled to room temperature to obtain a silicon / carbon aerogel composite material with a uniform carbon layer.
[0023] like Figures 6 to 8 As shown, the reaction vessel for preparing the black block hydrogel in step S2 includes a reaction vessel body 1, an annular plate 2, two sets of arc plates 3, a base 4, four sets of supports 5, a fixed plate 6, four sets of sliding rods 7, four sets of first sliders 8, a pressure plate 9, four sets of first springs 10, a hinge assembly, a buffer assembly, and a connecting assembly. An annular plate 2 is provided on the outer side of the reaction vessel body 1. The bottom ends of the annular plate 2 are respectively slidably fitted onto the top of the arc plates 3 via the buffer assembly. The bottoms of the two sets of arc plates 3 are respectively connected to the top of the base 4 via the connecting assembly. Four sets of supports 5 are evenly arranged on the bottom of the base 4. The bottom of the fixed plate 6 is connected to the top of the base 4. Four sets of sliding grooves are evenly arranged on the top of the fixed plate 6, and each of the four sets of fixed plate 6 sliding grooves is provided with a set of sliding rods 7. The first slider 8 is slidably connected to the fixed plate 6 via a set of sliding rods 7 and a set of first springs 10 at one end of the outer side of each of the four sets of sliding rods 7. The tops of the four sets of first sliders 8 are respectively hinged to the bottom of the pressure plate 9 via a hinge assembly, and the top of the pressure plate 9 is in close contact with the bottom of the reactor body 1. When vibration occurs, the reactor body will generate force and begin to compress the pressure plate. The four sets of first sliders will slide through the hinge assembly and begin to compress the first springs. During the extension and retraction of the four sets of first springs and the buffer assembly, the damage caused by the force generated by vibration can be effectively reduced, and the damage caused by the force to the reactor body can be reduced, thereby improving the efficiency and effect of preparing aerogel composite materials and thus enhancing practicality.
[0024] As a preferred embodiment of the above, the buffer assembly includes multiple sets of damping rods 11 and multiple sets of second springs 12. A set of grooves is provided at both ends of the bottom of the annular plate 2. The tops of the grooves of the two sets of annular plates 2 are uniformly connected to the tops of the multiple sets of damping rods 11. The tops of the two sets of arc-shaped plates 3 are connected to the bottoms of the multiple sets of damping rods 11. The tops of the two sets of arc-shaped plates 3 are slidably fitted into the bottom grooves of the annular plate 2. A set of second springs 12 is provided on the outer side of each set of damping rods 11. By having the multiple sets of damping rods drive the second springs to extend and retract, the damage caused by the force to the reactor body can be reduced, thereby improving the efficiency and effectiveness of preparing aerogel composite materials, thus enhancing practicality.
[0025] As a preferred embodiment of the above, the connecting assembly includes two sets of arc-shaped blocks 13, two sets of locking blocks 14, and two sets of connecting screws 15. Two sets of arc-shaped blocks 13 are evenly arranged on the top of the base 4. Each set of arc-shaped blocks 13 has a locking groove on its top. The bottoms of the two sets of locking blocks 14 are respectively engaged with the locking grooves of the arc-shaped blocks 13. The tops of the two sets of locking blocks 14 are connected to the bottom of the arc-shaped plate 3. Each set of locking blocks 14 has a threaded hole that penetrates through the arc-shaped blocks 13. The two sets of connecting screws 15 are threadedly connected to the locking blocks 14 and the arc-shaped blocks 13 through the threaded holes. By connecting the connecting screws through the locking blocks and the arc-shaped blocks, the workers can quickly install and disassemble the base and the support, thus enhancing practicality.
[0026] As a preferred embodiment of the above, the hinge assembly includes multiple sets of hinge seats 16 and four sets of support rods 17. The tops of the four sets of first sliders 8 are respectively hinged to one end of a set of hinge seats 16 and support rods 17, and the bottom of the pressure plate 9 is uniformly hinged to the other end of the four sets of hinge seats 16 and support rods 17. By hinged to the hinge seats and support rods, the four sets of first sliders can quickly compress the connecting spring, thereby reducing the damage caused by the force to the main body of the reactor, thus improving the efficiency and effect of preparing aerogel composite materials, and thus enhancing practicality.
[0027] As a preferred embodiment of the above, it also includes two sets of rotating handles 18, with one set of rotating handles 18 provided at one end of each of the two sets of connecting screws 15; this allows the operator to quickly rotate the connecting screws, thus enhancing practicality.
[0028] As a preferred embodiment of the above, it also includes four sets of anti-slip pads 19, with each of the four sets of supports 5 having a set of anti-slip pads 19 at its bottom; this can provide the anti-slip effect of the supports, prevent slippage from affecting the preparation effect, and thus enhance practicality.
[0029] As a preferred embodiment of the above, a sponge pad 20 is also included, and a set of sponge pads 20 are provided on the top of the pressure plate 9; this can reduce the damage to the reactor body caused by squeezing friction, thus enhancing practicality.
[0030] The working principle of the reactor of the present invention is as follows: when vibration occurs, the reactor body will generate force and begin to squeeze the pressure plate. Through the hinge seat and support rod, the four sets of first sliders slide and begin to squeeze the first spring. In the process of the four sets of first springs and multiple sets of damping rods driving the second spring to extend and retract, the damage caused by the force generated by vibration can be effectively reduced. Example 4
[0031] S1. Cut 7.32 parts by weight of orange peel into pieces of the same size, put them into an aqueous solution containing 3.11 parts by weight of melamine, stir at 150 r / min for 5 h at room temperature, soak for 12 h, and then place them in a forced-air drying oven to dry completely to obtain nitrogen-doped carbon precursor. S2. 5.21 parts by mass of nitrogen-doped carbon precursor and 1.74 parts by mass of nano-silicon (100nm) were added to deionized water and stirred at 200r / min for 0.5h at room temperature. The mixture was then transferred to a reaction vessel, sealed and placed in a constant temperature drying oven. The mixture was hydrothermally heated at 250℃ for 10h to obtain a black block hydrogel. S3. 3.48 parts by weight of black block hydrogel were washed with ethanol and placed in a freeze dryer for vacuum drying for 24 h to obtain black block aerogel. S4, 2.06 parts by mass of aerogel were heated to 800°C at a heating rate of 5°C / min and held for 1 hour under argon protection. Then, acetylene gas was introduced, and the temperature was further increased to 1200°C at a heating rate of 2°C / min and held for 2 hours. After carbonization and chemical vapor deposition, the mixture was cooled to room temperature to obtain a silicon / carbon aerogel composite material with a uniform carbon layer.
[0032] As shown in the figure Figure 1 This is a flowchart illustrating the preparation process of silicon / carbon aerogel composite materials. Figures 2-5 The charge-discharge curves are for the silicon / carbon aerogel composite materials prepared in Examples 1-4. Figure 9 The graph shows the cycling performance of the silicon / carbon aerogel composite materials prepared in Examples 1-4.
[0033] The silicon / carbon aerogel composites prepared in Examples 1-4 were subjected to constant current charge-discharge tests and cycle tests using an A211-BTS-4S-1U type device. Table 1 shows the charge-discharge capacity and first-cycle efficiency of the silicon / carbon aerogel composites. Table 2 shows the cycle capacity retention of the silicon / carbon aerogel composites.
[0034]
[0035]
[0036] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A method for preparing a silicon / biomass carbon aerogel composite material for lithium-ion battery anodes, characterized in that... Includes the following steps: S1. Cut 5.28–7.32 parts by weight of fruit peel into pieces of the same size, place them in an aqueous solution containing 2.42–3.11 parts by weight of melamine, stir at 100–150 r / min for 2–5 hours at room temperature, soak, and then place in a forced-air drying oven to dry completely to obtain a nitrogen-doped carbon precursor; the fruit peel is at least one of orange peel, grapefruit peel, watermelon peel, and tangerine peel; S2. 3.85-5.21 parts by mass of nitrogen-doped carbon precursor and 1.28-1.74 parts by mass of 10-100 nm nano-silicon were added to deionized water. After stirring at 150-200 r / min for 0.5-2 h at room temperature, the mixture was transferred to a reaction vessel and placed in a constant temperature drying oven. The mixture was then hydrothermally heated at 120-250 °C for 10-20 h to obtain a black block hydrogel. S3. Wash 2.53 to 3.48 parts by weight of black block hydrogel with ethanol and / or deionized water, and then place it in a freeze dryer and vacuum dry for 20 to 24 hours to obtain black block aerogel. S4, 1.45-2.06 parts by mass of aerogel are carbonized and chemically vapor-deposited, then cooled to room temperature to obtain a silicon / carbon aerogel composite material with a uniform carbon layer. The carbonization is specifically carried out by heating to 600-800°C at a heating rate of 5°C / min and holding for 1-3 hours under an inert atmosphere. The chemical vapor deposition is specifically carried out by introducing an organic gas under an inert atmosphere and heating to 900-1200°C at a heating rate of 2°C / min and holding for 2-4 hours. The inert gas is at least one of nitrogen and argon, and the organic gas is acetylene.
2. The method for preparing a silicon / biomass carbon aerogel composite material for a lithium-ion battery negative electrode according to claim 1, characterized in that: Step S2: A reaction vessel for preparing black block hydrogel, comprising a reaction vessel body (1), characterized in that it further comprises an annular plate (2), two sets of arc plates (3), a base (4), four sets of supports (5), a fixing plate (6), four sets of slide rods (7), four sets of first sliders (8), a pressure plate (9), four sets of first springs (10), a hinge assembly, a buffer assembly, and a connecting assembly. A set of annular plates (2) is provided on the outside of the reaction vessel body (1). The bottom ends of the annular plates (2) are respectively slidably fitted through the buffer assembly and the top of the arc plates (3), and the bottoms of the two sets of arc plates (3) are respectively connected through the connecting assembly and the base (6). 4) Top connection, four sets of supports (5) are evenly arranged at the bottom of the base (4), the bottom of the fixing plate (6) is connected to the top of the base (4), four sets of sliding grooves are evenly arranged at the top of the fixing plate (6), and a set of sliding rods (7) are respectively arranged in the four sets of sliding grooves of the fixing plate (6). The four sets of first sliders (8) are slidably connected through a set of sliding rods (7) and the sliding grooves of the fixing plate (6). A set of first springs (10) is respectively arranged at one end of the outer side of the four sets of sliding rods (7). The tops of the four sets of first sliders (8) are respectively hinged to the bottom of the pressure plate (9) through the hinge assembly, and the top of the pressure plate (9) is in close contact with the bottom of the reactor body (1).
3. The method for preparing a silicon / biomass carbon aerogel composite material for a lithium-ion battery negative electrode according to claim 2, characterized in that: The buffer assembly includes multiple sets of damping rods (11) and multiple sets of second springs (12). A set of grooves is provided at both ends of the bottom of the annular plate (2). The tops of the grooves of the two sets of annular plates (2) are evenly connected to the tops of the multiple sets of damping rods (11). The tops of the two sets of arc plates (3) are connected to the bottoms of the multiple sets of damping rods (11). The tops of the two sets of arc plates (3) are slidably fitted into the bottom grooves of the annular plate (2). A set of second springs (12) is provided on the outer side of the multiple sets of damping rods (11).
4. The method for preparing a silicon / biomass carbon aerogel composite material for a lithium-ion battery negative electrode according to claim 2, characterized in that: The connecting components include two sets of arc blocks (13), two sets of locking blocks (14) and two sets of connecting screws (15). Two sets of arc blocks (13) are evenly arranged on the top of the base (4). Each set of arc blocks (13) has a locking groove on its top. The bottom of each set of locking blocks (14) is engaged with the locking groove of the arc blocks (13). The top of each set of locking blocks (14) is connected to the bottom of the arc plate (3). Each set of locking blocks (14) has a threaded hole through the arc blocks (13). The two sets of connecting screws (15) are threadedly connected to the locking blocks (14) and the arc blocks (13) through the threaded holes.
5. The method for preparing a silicon / biomass carbon aerogel composite material for a lithium-ion battery negative electrode according to claim 2, characterized in that: The hinge assembly includes multiple sets of hinge seats (16) and four sets of support rods (17). The tops of the four sets of first sliders (8) are respectively hinged through one set of hinge seats (16) and one end of the support rods (17), and the bottom of the pressure plate (9) is evenly hinged through the other end of the four sets of hinge seats (16) and support rods (17).
Citation Information
Patent Citations
Preparation method of lithium-ion battery silicon / carbon composite aerogel cathode material
CN109755507A
Method for preparing lithium ion battery silicon-carbon composite negative electrode material by taking konjac flour as carbon source
CN108565431A
Polycarboxylate superplasticizer reaction kettle convenient to clean
CN220759234U
